Soil, territory, land: The spatial politics of settler organic farming in the West Bank, Israel/Palestine. (October 2021) - Grosglik, Rafi; Handel, Ariel; Monterescu, Daniel
In settler colonial settings, agriculture is a means of reclaiming territorial sovereignty and indigenous identity. Turning attention to the Jewish settlers in the West Bank and their multiple uses and abuses of organic farming, this article explores epistemic and political spatial operations on the colonial frontier. Applying a relational conceptualization of three spatial modalities—soil, territory, and land—we explore the ways in which these modalities serve as political apparatuses: Soil designates the romantic perception of cultivable space, territory is concerned with borders and political sovereignty, and land is seen as a space of economic value and as a means of production. While agriculture is a well-known instrument of expansion and dispossession, organic farming contributes to the colonial operation by binding together affective attachment to the place, and new economic singularity in relation to environmental and ethical claims. We argue that organic farming practices converge claims for local authenticity, spatial appropriation, and high economic values that are embedded in what we term the colonial quality turn . Ultimately, organic farming in the West Bank normalizes the inherent violence of the colonial project and strengthens the settlers' claim for political privilege.